The influence of urban environmental effects on the orchard soil microbial community structure and function: a case study in Zhejiang, China - Dai, Rongchen; Jin, Cuixiang; Xiao, Meng (Frontiers in Microbiology, 2024)
The urban environmental effects can have multifaceted impacts on the orchard soil microbial community structure and function. To specifically study these effects, we investigated the soil bacterial and fungal community in the laxly managed citrus orchards using amplicon sequencing. Ascomycota demonstrated significant dominance within the citrus orchard soils. The increased presence of beneficial Trichoderma spp. (0.3%) could help suppress plant pathogens, while the elevated abundance of potential pathogenic fungi, such as Fusarium spp. (0.4%), might raise the likelihood of disorders like root rot, thereby hindering plant growth and resulting in reduced yield. Moreover, we observed significant differences in the alpha and beta diversity of bacterial communities between urban and rural soils (p < 0.001). Environmental surveys and functional prediction of bacterial communities suggested that urban transportation factors and rural waste pollution were likely contributing to these disparities. When comparing bacterial species in urban and rural soils, Bacillus spp. exhibited notable increases in urban areas. Bacillus spp. possess heavy metal tolerance attributed to the presence of chromium reductase and nitroreductase enzymes involved in the chromium (VI) reduction pathway. Our findings have shed light on the intricate interplay of urban environmental effects and root systems, both of which exert influence on the soil microbiota. Apart from the removal of specific pollutants, the application of Bacillus spp. to alleviate traffic pollution, and the use of Trichoderma spp. for plant pathogen suppression were considered viable solutions. The knowledge acquired from this study can be employed to optimize agricultural practices, augment citrus productivity, and foster sustainable agriculture.